The IASLC Lung Cancer Staging Project: Background Data and Proposals for the Application of TNM Staging Rules to Lung Cancer Presenting as Multiple Nodules with Ground Glass or Lepidic Features or a Pneumonic Type of Involvement in the Forthcoming Eighth Edition of the TNM Classification. Issue 5 (May 2016) - Detterbeck, Frank C.; Marom, Edith M.; Arenberg, Douglas A.; Franklin, Wilbur A.; Nicholson, Andrew G.; Travis, William D.; Girard, Nicolas; Mazzone, Peter J.; Donington, Jessica S.; Tanoue, Lynn T.; Rusch, Valerie W.; Asamura, Hisao; et al.
ABSTRACT : Introduction: : Application of tumor, node, and metastasis (TNM) classification is difficult in patients with lung cancer presenting as multiple ground glass nodules or with diffuse pneumonic‐type involvement. Clarification of how to do this is needed for the forthcoming eighth edition of TNM classification. Methods: : A subcommittee of the International Association for the Study of Lung Cancer Staging and Prognostic Factors Committee conducted a systematic literature review to build an evidence base regarding such tumors. An iterative process that included an extended workgroup was used to develop proposals for TNM classification. Results: : Patients with multiple tumors with a prominent ground glass component on imaging or lepidic component on microscopy are being seen with increasing frequency. These tumors are associated with good survival after resection and a decreased propensity for nodal and extrathoracic metastases. Diffuse pneumonic‐type involvement in the lung is associated with a worse prognosis, but also with a decreased propensity for nodal and distant metastases. Conclusion: : For multifocal ground glass/lepidic tumors, we propose that the T category be determined by the highest T lesion, with either the number of tumors or m in parentheses to denote the multifocal nature, and that a single N and M category be used for all the lesions collectively—for example, T1a(3)N0M0 or T1b(m)N0M0. For diffuse pneumonic‐type lung cancer we propose that the T category be designated by size (or T3) if in one lobe, as T4 if involving an ipsilateral different lobe, or as M1a if contralateral and that a single N and M category be used for all pulmonary areas of involvement.